Mayo Clinic guide to a healthy pregnancy - Wick, Myra; Mayo Clinic (Rochester, MN : Mayo Clinic, 2018)
"Mayo Clinic Guide to a Healthy Pregnancy has become a trusted resource for parents-to-be. In this fully reviewed and revised second edition, you'll find updated guidance and practical tips, including: Evidence-based medical advice for parents from a world-class team of doctors and care providers; Information on pregnancy planning and fertility; Weekly updates on baby's growth and development; Monthly explanation of changes for mom; Guidance on nutrition, exercise and weight gain; Tips for working, traveling and managing parenthood; Reliable information on recent trends and technologies in pregnancy and postpartum care; Answers to difficult or embarrassing questions"--
part 1. Enjoying a healthy pregnancy. Preparing to become pregnant ; Healthy choices during pregnancy ; For dads and partners -- part 2. Pregnancy month by month. Months 1-10 ; Labor and childbirth ; Cesarean birth -- part 3. Baby is finally home. Your newborn ; Taking baby home ; Postpartum issues for mom ; Managing as parents -- part 4. Important decisions of pregnancy. Genetic screening ; Prenatal testing ; Breast-feeding ; Pain relief during childbirth ; Elective cesarean births ; Vaginal birth after a cesarean birth ; Contraception after delivery -- part 5. Symptoms guide -- Part 6. Complications of pregnancy and childbirth. Issues during pregnancy ; Problems of labor and childbirth ; Managing mom's health concerns ; Pregnancy loss.
"Fully revised and updated"--Cover.
Includes index.
Keywords: Pregnancy; Prenatal care; Childbirth